ALTERNATIF PEMANFAATAN LIMBAH INDUSTRI PENGOLAHAN KAYU SEBAGAI ARANG BRIKET - Usman Malik (Jurnal APTEK, 2013)
Waste is meant here is a byproduct formed from woody biomass material events or ligno-cellulose fiber, a material that has not been utilized. For this case is limited to the wood processing industry.The presence of waste treatment is a problem that has been left to rot, piled and burned all of which have a negative impact on the environment so that mitigation should be considered. One way that can be taken is to use a value-added product with the applied technology and democracy so that the results are easily disseminated to the public. Evaluation results show some positive prospects as an example of applied technology can be applied satisfactorily defined in converting industrial waste into charcoal powder processing wood, charcoal briquettes, charcoal, charcoal, compost and soil conditioning.Application of applied technology and democracy can be developed into a large-scale (pilot and commercial) both technically and economically.